2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6225045
|View full text |Cite
|
Sign up to set email alerts
|

Using depth and appearance features for informed robot grasping of highly wrinkled clothes

Abstract: Detecting grasping points is a key problem in cloth manipulation. Most current approaches follow a multiple regrasp\ud strategy for this purpose, in which clothes are sequentially grasped from different points until one of them yields to a\ud desired configuration. In this paper, by contrast, we circumvent the need for multiple re-graspings by building a robust detector that identifies the grasping points, generally in one single step,\ud even when clothes are highly wrinkled.\ud In order to handle the large v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 14 publications
0
81
0
1
Order By: Relevance
“…In the hanged shirt the sleeves are identifiable as well. Previous works have shown that this 3D structure can be used to identify wrinkles [56] and also the collar structure, using computer vision algorithms [57].…”
Section: Object-related Tasksmentioning
confidence: 99%
“…In the hanged shirt the sleeves are identifiable as well. Previous works have shown that this 3D structure can be used to identify wrinkles [56] and also the collar structure, using computer vision algorithms [57].…”
Section: Object-related Tasksmentioning
confidence: 99%
“…In that regard, Ramisa et al [8] propose a supervised learning approach for grasping highly wrinkled garments. In Ramisa's grasp point detection method, manually segmented regions are used to train logistic regression and χ 2 SVM classifiers using bag-of-words descriptors based on SIFT [10] and Geodesic-Depth Histogram features [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on perception and manipulation tasks for robotic laundry systems consists of: isolating and classifying clothes from a laundry heap [8,5,9], finding a tractable state of the clothes in order to interact and manipulate them [3] and then folding the cloth [1,2,5]. In that regard, Ramisa et al [8] propose a supervised learning approach for grasping highly wrinkled garments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is an extension of Ramisa et al [4,5] where a preliminary version of the part detection pipeline and the FINDDD descriptor were presented, respectively. The current paper combines and extends both previous contributions in a pipeline for garment manipulation, and it provides a more thorough mathematical description of the methods used, as well as a more extensive set of evaluations (e.g.…”
Section: Introductionmentioning
confidence: 99%